PEMBERIAN INSENTIF PAJAK BAGI PELAKU UMKM DI MASA PANDEMI COVID 19 - Ainun Arizah; Khadijah Darwin; Nurul Fuada (ITB AAS INDONESIA, 2022)
Abstract The COVID-19 pandemic that is felt throughout the world has had a significant impact on almost all levels of society. The Indonesian government has issued various policies to maintain economic stability. MSME actors as taxpayers are required to report their monthly business realization reports if they want to get tax incentives. This study focuses on understanding the application of PMK No. 9 of 2021 regarding MSME tax incentives borne by the government. In this case, how MSMEs interpret the existence of these tax incentives for the sustainability of their business. This study uses a qualitative method in the form of a case study by conducting interviews with related informants. The results of the study found that government policies provide tax incentives for MSME actors by issuing PMK No. 9 of 2021 was carried out as a positive response to the government seeing the continuity of MSME businesses which began to falter during the Covid 19 pandemic. The culinary sector was chosen because culinary is one of the basic needs which certainly generates considerable profits compared to other sectors. The Covid 19 pandemic that was felt by the culinary sector MSMEs made them also have to experience economic difficulties. Access to information that is not as 'open' as access to other information related to tax incentives makes MSME actors not access this information at the beginning of the policy and the use of tax incentives from the government is still quite burdensome for MSME actors because of the requirement to report monthly business realization reports. Keywords : COVID – 19, Insentif Pajak, UMKM